2024
DOI: 10.3390/app14031295
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Argon Solid Phases Formed from the Liquid State at Different Isobaric Cooling Rates

Eugeny I. German,
Shulun B. Tsydypov,
Michael I. Ojovan
et al.

Abstract: By the method of molecular dynamics, computer simulation of the processes of isobaric cooling of argon particle systems under initial conditions with a temperature of 150 K at pressure values from 0.1 to 4 MPa to a temperature of 40 K with cooling rates of 108, 109, 1010, 1011 and 1012 K/s was performed. As a result of a computer experiment, coordinate arrays of particles were obtained, which were subjected to the procedure of three-dimensional Voronoi partitioning to identify and calculate the number of eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…However, it is unambiguously revealed that the higher the pressure, the lower the effective masses of the flowing units. This trend is explicitly shown in Figure 5 for argon, the interest in structural changes of which, at varying pressures, is not diminishing, demonstrating the existence of crystalline clusters within the background of an amorphous phase, even at ultra-fast cooling rates [28].…”
Section: Effective Masses Of Flowing Unitsmentioning
confidence: 75%
“…However, it is unambiguously revealed that the higher the pressure, the lower the effective masses of the flowing units. This trend is explicitly shown in Figure 5 for argon, the interest in structural changes of which, at varying pressures, is not diminishing, demonstrating the existence of crystalline clusters within the background of an amorphous phase, even at ultra-fast cooling rates [28].…”
Section: Effective Masses Of Flowing Unitsmentioning
confidence: 75%